Diazotrophic Bacteria Pantoea dispersa and Enterobacter asburiae Promote Sugarcane Growth by Inducing Nitrogen Uptake and Defense-Related Gene Expression - Singh, Pratiksha; Singh, Rajesh Kumar; Li, Hai-Bi; Guo, Dao-Jun; Sharma, Anjney; Lakshmanan, Prakash; Malviya, Mukesh K.; Song, Xiu-Peng; Solanki, Manoj K.; Verma, Krishan K.; Yang, Li-Tao; Li, Yang-Rui (Frontiers in Microbiology, 2021)
Sugarcane is a major crop in tropical and subtropical regions of the world. In China, the application of large amounts of nitrogen (N) fertilizer to boost sugarcane yield is commonplace but it causes substantial environmental damages, particularly soil and water pollution. Certain rhizosphere microbes are known to be beneficial for sugarcane production but much of the sugarcane rhizosphere microflora remains unknown. We have isolated several sugarcane rhizosphere bacteria and 27 of them were examined for N-fixation, plant growth promotion, and antifungal activity. 16S rRNA gene sequencing was used to identify these strains. Among the isolates, several strains were found to have a relatively high activity of nitrogenase and ACC deaminase, the enzyme that reduces ethylene production in plants. These strains were found to possess nifH and acdS genes associated with N-fixation and ethylene production, respectively. Two of these strains, Pantoea dispersa-AA7 and Enterobacter asburiae-BY4 showed maximum plant growth promotion (PGP) and nitrogenase activity, and thus they were selected for detailed analysis. The results show that they colonize different sugarcane tissues, use various growth substrates (carbon and nitrogen), and tolerate various stress conditions (pH and osmotic stress). The positive effect of AA7 and BY4 strains on nifH and stress-related genes (SuCAT, SuSOD, SuPAL, SuCHI, and SuGLU) expression and the induction of defense-related processes in two sugarcane varieties, GT11 and GXB9, showed their potential for stress amelioration and PGP. Both bacterial strains increased several sugarcane physiological parameters i.e., plant height, shoot weight, root weight, leaf area, chlorophyll content, and photosynthesis in plants grown under greenhouse condition. The ability of rhizobacteria on N-fixing in sugarcane was also confirmed by 15N isotope-dilution study and the estimate indicate a contribution of 21-35% of plant nitrogen by rhizobacterial biological N fixation (BNF). This is the first report of sugarcane growth promotion by N-fixing rhizobacteria P. dispersa and E. asburiae strains. Both strains could be used as biofertilizer for sugarcane to minimize nitrogen fertilizer use and better disease management.